Study on Mechanical and Dielectric Properties of 1, 3, Dimethyl Urea Doped L-Arginine Phosphate Monohydrate Single Crystals - Pratik M. Wankhade (International Journal of Scientific Research in Science and Technology, 2024)
Single crystals of pure and 1mol% 1,3-dimethyl urea doped L-arginine phosphate monohydrate were grown from solution by a slow solvent evaporation method. Grown crystals were subjected to the dielectric measurement study in the frequency range 1 KHz-1MHz at various temperatures. The dielectric constants and dielectric losses have been determined.  The temperature and frequency dependence of dielectric constant and dielectric loss has been discussed. Other parameters like ac conductivity has been estimated and presented in present work.Hardness study confirms the doped LAP crystal have moderate hardness value.
Keywords: Dielectric Constant; Mechanical; Ac Conductivity